2006
DOI: 10.1016/j.anihpc.2005.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Corner defects in almost planar interface propagation

Abstract: We study existence and stability of interfaces in reaction-diffusion systems which are asymptotically planar. The problem of existence of corners is reduced to an ordinary differential equation that can be viewed as the travelling-wave equation to a viscous conservation law or variants of the Kuramoto-Sivashinsky equation. The corner typically, but not always, points in the direction opposite to the direction of propagation. For the existence and stability problem, we rely on a spatial dynamics formulation wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
69
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 68 publications
(70 citation statements)
references
References 58 publications
0
69
0
1
Order By: Relevance
“…In Section 2, we simplify the existence problem using an equivariant spatial center-manifold reduction, inspired by the general approach to almost planar waves developed in [9] for reaction-diffusion systems; see also [10,11]. In Section 3, we then analyze the reduced system of ordinary differential equations.…”
Section: Outlinementioning
confidence: 99%
See 2 more Smart Citations
“…In Section 2, we simplify the existence problem using an equivariant spatial center-manifold reduction, inspired by the general approach to almost planar waves developed in [9] for reaction-diffusion systems; see also [10,11]. In Section 3, we then analyze the reduced system of ordinary differential equations.…”
Section: Outlinementioning
confidence: 99%
“…Following the general approach in [9] we start by rewriting this equation as a first order system in which x is the time-like variable. This is easily achieved by taking u = (u,…”
Section: Reduction To a Spatial Center-manifoldmentioning
confidence: 99%
See 1 more Smart Citation
“…All these nonplanar fronts share the property that the asymptotic planar part of the front propagates towards the middle, center part of the interface. The results in [8] show that, at least for small angles ε, the existence and asymptotic stability of these interior corners is a universal feature in isotropic reaction-diffusion systems, u ∈ R N , that exhibit stable planar fronts. We point out that unstable, or pulsating, fronts may lead to different types of interfaces such as exterior corners, steps, or holes; see Figure 2.1.…”
Section: Introductionmentioning
confidence: 92%
“…Planar fronts connecting the stable homogeneous equilibria u = 0 and u = 1 may propagate in either direction n = (sin ϕ, cos ϕ), depending upon the initial condition. In a recent article [8], we showed that almost planar fronts exist for a = 1/2: the front position, traced for example by the level set u −1 (1/2), is located on a curve that approaches two straight lines y = ε|x| for ε > 0 small, and the interface propagates in the direction of increasing y.…”
Section: Introductionmentioning
confidence: 99%